Book Review "The Making of Mexican Modernist Architecture" (REVISTA NODO, 2024)
The modern movement is adopted in post-revolutionary Mexico, creating an architecture with a unique identity. The review presented analyzes the content of the book "The Making of Mexican Modernist Architecture", offering a tour of its content.
Keywords: Modern arquitecture; Mexico